(untitled) (Research, Society and Development, 2020)
Lectins are a special group of proteins with peculiar characteristics, these bind to carbohydrates of non-immunological origin. Several lectins have already been purified and isolated in nature, including in humans, they play very important roles especially in the process of innate immunity and cell signaling. Based on this information and given the importance of studying this class of proteins, this integrative review proposes to demonstrate the main references in the studies of lectins and their possible activities within the field of virology, being this object of study an important tool in the treatment of viral infections. The data show that in the last 5 years (2015-2020), not only the discovery of new lectins with potential antivirals was made, but studies of structural improvement and modification of the vector / virus link when applicable. It is concluded that the lectins approach a viable alternative of study and knowledge in the treatment of several diseases caused by viruses in different classes and animal species.